Economic Liberalisation and Development in Africa. - Jomo K. S. (Jomo Kwame Sundaram) (CODESRIA, 2008)
Sundaram notes that over three decades of economic stagnation, contraction and increased poverty have taken a huge toll on Africa's economic, social and political fabric; and pro-active efforts are urgently required in order to build new capacities and c.